PREVALENCE, MANAGEMENT AND OUTCOME OF CERVICAL CANCER IN LOW INCOME COUNTRIES : A COMPREHENSIVE SYSTEMATIC REVIEW - Rifqian, Naufal; Reza Hidayat, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Cervical cancer intervention focuses on primary and secondary prevention. Primary prevention and screening are the best methods to decrease the burden of cervical cancer and mortality. The aim: The aim of this study to show about prevalence, management and outcome of cervical cancer in low income countries. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The disease burden of cervical cancer has decreased significantly in developed countries and regions in last decades, however it is still serious in less developed countries and regions, and effective preventive measures in these areas still face serious challenges.